The effects of physical activity interventions on psychosocial outcomes in adolescents: A meta-analytic review. (April 2016) - Spruit, Anouk; Assink, Mark; van Vugt, Eveline; van der Put, Claudia; Stams, Geert Jan
Abstract: Physical activity interventions are often implemented in the adolescent mental health care practice to prevent or treat psychosocial problems. To date, no systematic review of the effect of these physical activity interventions in adolescents has been conducted. In the current study, four multilevel meta-analyses were performed to assess the overall effect of physical activity interventions on externalizing problems, internalizing problems, self-concept, and academic achievement in adolescents. In addition, possible moderating factors were examined. In total, 57 studies reporting on 216 effect sizes were included, and the results showed significant small-to-moderate effects of physical activity interventions on externalizing problems ( d = 0.320), internalizing problems ( d = 0.316), self-concept ( d = 0.297), and academic achievement ( d = 0.367). Further, moderator analyses showed that outcome, study, sample, and intervention characteristics influenced the effects of physical activity interventions on psychosocial outcomes. Implications for theory and practice concerning the use of physical activity interventions in adolescent mental health care practice are discussed. Highlights: Four meta-analyses on the effects of physical activity interventions were conducted. Significant effects of physical activity were found on all psychosocial outcomes. Physical activity interventions can be effective in reducing psychosocial problems. Effects depend on several outcome, study, sample and intervention characteristics.